Productive performance and intestinal morphometry of broilers subjected to diets including spirulina (Arthrospira platensis) - Fuentes N., Nadia (2023)
The aim of this study was to determine the effect of spirulina (Arthrospira platensis) on productive performance (WG: weight gain, FI: feed intake, FCR: feed conversion ratio, EPEI: European productive efficiency index) and intestinal morphometry (VL: villus length,  VW: villus width, CD: crypt depth) in broilers. In total, 240 one-day-old male chicks from the Cobb 500 line were used, distributed into four treatments with six replicates of 10 chicks each. The treatments were: T0: base diet without spirulina (control), T1: base diet with 0.25% spirulina, T2: base diet with 0.5% spirulina, T3: base diet with 1% spirulina. A completely randomized block design was used. The effect of increasing levels of spirulina was evaluated by linear and quadratic polynomial orthogonal contrasts. The WG and FI variables showed quadratic trend while FCR and EPEI showed linear trend. The optimal level of spirulina that maximizes weight gain was 0.68% with a predictive value of 3330 g. The increasing levels of spirulina did not affect the morphometric measurements of VL and VW at the level of duodenum, jejunum and ileum; therefore, significant linear responses were obtained in CD and VL/CD in jejunum and in VL/CD in ileum as a response to the increasing levels of spirulina in the diet. It was concluded that the increasing levels of spirulina influence the productive performance under experimental conditions while they were not conclusive for intestinal morphometry in Cobb 500 chicks at 42 days of age.